2017
DOI: 10.18632/oncotarget.21706
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA PVT1 inhibits renal cancer cell apoptosis by up-regulating Mcl-1

Abstract: Long non-coding RNA plasmacytoma variant translocation 1 (PVT1) is up-regulated in various human cancers, and our results indicated that PVT1 was up-regulated in clear cell renal cell carcinoma tissues. The Cancer Genome Atlas cohort analysis revealed that in clear cell renal cell carcinoma, higher PVT1 expression correlated with advanced TNM stage, histological grade, and poor survival. PVT1 knockdown promoted apoptosis, inhibited renal cancer cell proliferation, decreased Mcl-1, and increased cleaved caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 30 publications
3
38
1
Order By: Relevance
“…It has been validated that lncRNA AK001796 could act as an effective treatment target and underlying prognostic factor for esophageal squamous cell carcinoma (ESCC) (Liu et al, 2018a). Interestingly, Wu et al also revealed that overexpressed lncRNA PVT1 was related to tumorigenesis and poor prognosis in cancers (Wu et al, 2017). In addition, FSCN1 was expressed at a high level in ESCC (Shang et al, 2018), and overexpression of FSCN1 led to poor prognosis in ESCC (Akanuma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been validated that lncRNA AK001796 could act as an effective treatment target and underlying prognostic factor for esophageal squamous cell carcinoma (ESCC) (Liu et al, 2018a). Interestingly, Wu et al also revealed that overexpressed lncRNA PVT1 was related to tumorigenesis and poor prognosis in cancers (Wu et al, 2017). In addition, FSCN1 was expressed at a high level in ESCC (Shang et al, 2018), and overexpression of FSCN1 led to poor prognosis in ESCC (Akanuma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA UCA1 was reported to function as an oncogene in RCC through directly interacting with miR‐495 . Wu and colleagues indicated that lncRNA PVT1 knockdown promoted apoptosis, inhibited proliferation of RCC cells through enhancing Mcl‐1 mRNA stability . In the present study, we demonstrated that NBAT1 was significantly decreased in RCC cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…Plasmacytoma variant translocation 1 (PVT1) is transcribed from a locus adjacent to the MYC locus on human chromosome 8q24 [72]. The PVT1 is known to be up-regulated in some human tumors, such as HCC, ovarian cancer, malignant pleural mesothelioma, non-small cell lung cancer and renal cancer [122][123][124][125][126].…”
Section: Pvt1mentioning
confidence: 99%